Modeling seizures in the Human Phenotype Ontology according to contemporary ILAE concepts makes big phenotypic data tractable. (5th May 2021) - Lewis‐Smith, David; Galer, Peter D.; Balagura, Ganna; Kearney, Hugh; Ganesan, Shiva; Cosico, Mahgenn; O'Brien, Margaret; Vaidiswaran, Priya; Krause, Roland; Ellis, Colin A.; Thomas, Rhys H.; Robinson, Peter N.; et al.
Abstract: Objective: The clinical features of epilepsy determine how it is defined, which in turn guides management. Therefore, consideration of the fundamental clinical entities that comprise an epilepsy is essential in the study of causes, trajectories, and treatment responses. The Human Phenotype Ontology (HPO) is used widely in clinical and research genetics for concise communication and modeling of clinical features, allowing extracted data to be harmonized using logical inference. We sought to redesign the HPO seizure subontology to improve its consistency with current epileptological concepts, supporting the use of large clinical data sets in high‐throughput clinical and research genomics. Methods: We created a new HPO seizure subontology based on the 2017 International League Against Epilepsy (ILAE) Operational Classification of Seizure Types, and integrated concepts of status epilepticus, febrile, reflex, and neonatal seizures at different levels of detail. We compared the HPO seizure subontology prior to, and following, our revision, according to the information that could be inferred about the seizures of 791 individuals from three independent cohorts: 2 previously published and 150 newly recruited individuals. Each cohort's data were provided in a different format and harmonized using the two versions of the HPO. Results: The new seizure subontology increased the number of descriptive concepts for seizures 5‐fold. The number of seizure descriptors that could be annotated to the cohort increased by 40% and the total amount of information about individuals' seizures increased by 38%. The most important qualitative difference was the relationship of focal to bilateral tonic‐clonic seizure to generalized‐onset and focal‐onset seizures. Significance: We have generated a detailed contemporary conceptual map for harmonization of clinical seizure data, implemented in the official 2020‐12‐07 HPO release and freely available at hpo.jax.org. This will help to overcome the phenotypic bottleneck in genomics, facilitate reuse of valuable data, and ultimately improve diagnostics and precision treatment of the epilepsies.